(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
One noninvasive technique that shows promise in the detection of superficial femoral artery blockage in peripheral vascular disease is Doppler sonography.Methods The 50 patients included in this prospective study had Doppler sonography and multidetector CT scans performed at the Cardiac Center in Al-Sadir Medical City, Al-Najaf, over the course of eight months, beginning in December 2011 and ending on August 2012. Results reveal that the Doppler study’s sensitivity(92.5%), specificity(100%), positive predictive value(100%), negative predictive value(76.9%), and accuracy (94%). All of these metrics are consistent with previous work on the identification of stenosis in patients. Conclusion: duplex scanning has several benefits, such as being noninvasive, inexpensive, capable of doing multilayer evaluations, and assessing wall morphology, surrounding structures, intraluminal structures, and plaque.It would suggest that individuals with peripheral artery occlusive disease may be reliably and accurately assessed by multi-detector row CT angiography. Aim of study: The purpose of this research is to compare the diagnostic accuracy of Doppler sonography and CT angiography for the detection of superficial femoral artery (SFA) blockage.